Pengaruh Kepemimpinan Terhadap Kinerja Karyawan di PT. Mitra Bumi Gemilang Kota Jambi - Andi Amelia Hastri (Science of Management and Students Research Journal (SMS), 2022)
The Effect of Leadership on Employee Performance at PT Bumi Gemilang Jambi City. This study aims to find out how the influence of leadership on employee performance at PT Bumi Gemilang, Jambi City. The population in this study are all employees within the scope of PT. Mitra Gemilang, City of Jambi, totaling 45 people. Data collection was carried out using documentation methods and questionnaires. The data analysis technique used is descriptive statistical analysis, and the hypothesis is tested by simple linear regression analysis. The linear regression equation formed Y = 18,353 + 0.453 X. Constant (a) = 18.353 This means that if the independent variable (leadership style) is considered equal to zero (0), then the value of the dependent variable (employee performance) is 18.353. Leadership Style (X) = +0.453 The coefficient value of the leadership style variable has a positive sign on employee performance with a regression coefficient value of 0.453. This shows that each value of the leadership style variable is increased by 1 point or a temporary unit, then the employee performance variable will increase by 0.453. It shows that leadership style has a positive and significant effect on employee performance due to a significance value of 0.000 <0.05. So that it can be said based on the results of testing the hypothesis that leadership style influences employee performance by 28.9% and the rest is influenced by other variables. It is suggested to further researchers to broaden the object of research so as to obtain more complete and broader information regarding the influence of leadership style on employee performance.